ACFTA (ASEAN -CHINA Free Trade Area): Menguntungakan Atau Merugikan Indonesia ? Ditinjau dari Perspektif Neoliberalisme - Sinta Julina (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2022)
The background of the research is that globalization causes rapid changes in various dimensions in international relations, so that countries in the world absolutely must cooperate between countries. Similarly with countries in Southeast Asia (ASEAN) and China, they believe that international cooperation can provide strength to face regionalism and economic blocs. Therefore they agreed to carry out free trade cooperation ACFTA then inaugurated the free trade of ASEAN and China in January 2010. In November 2018 President Joko Widodo finally ratified the